2001
DOI: 10.1046/j.0007-1323.2001.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of thoracic duct injuries after oesophagectomy

Abstract: The thoracic duct should be ligated during oesophagectomy. A high index of suspicion for duct injury must be maintained in all patients after operation. A policy of very early thoracic duct ligation at 48 h from diagnosis is proposed for duct injury if aggressive conservative management fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 67 publications
(52 reference statements)
1
88
0
7
Order By: Relevance
“…If chyle is not stopped, patients will faced immune deficiency, resulting in infection and mortality (35). Some studies have shown the superiority of surgery over conservative treatment (34,(38)(39)(40). Thus, the treatment method of Chylothorax is conservative but when the outlet of the chest tube is more than 800 cc per day and it will continue for 4 to 5 consecutive days, waiting for stopping the leak may be dangerous due to leukopenia and malnutrition; therefore, surgery is required in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…If chyle is not stopped, patients will faced immune deficiency, resulting in infection and mortality (35). Some studies have shown the superiority of surgery over conservative treatment (34,(38)(39)(40). Thus, the treatment method of Chylothorax is conservative but when the outlet of the chest tube is more than 800 cc per day and it will continue for 4 to 5 consecutive days, waiting for stopping the leak may be dangerous due to leukopenia and malnutrition; therefore, surgery is required in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In scientific terms, the weaknesses of this report are the fact that a rupture of the cysterna chyli was not definitively identified and we did not obtain laboratory confirmation that the fluid was chyle. Little has been published on isolated injuries of this sort [1][2][3][4] . In thoracic duct injuries, however, persistent loss of chyle has serious complications including death 5 .…”
Section: Commentmentioning
confidence: 99%
“…When alendronate is given for only six weeks at doses of 5-40 mg per day to postmenopausal women, PTH returns to baseline within as little as three months 1 . Symptomatic hypocalcaemia has been reported in patients treated with alendronate for osteoporosis or Paget's disease, usually because of unrecognized post-surgery hypoparathyroidism [2][3][4] . To our knowledge it has not been described before in the context of vitamin D deficiency and secondary hyperparathyroidism.…”
mentioning
confidence: 99%
“…Foreign bodies in the nose are seen mainly in young children who have inserted them deliberately 1,2 . Batteries are especially troublesome, because of their erosive effects 3 .…”
Section: Commentmentioning
confidence: 99%
“…The inert nature of the plastic did, however, mean that there was little tissue reaction of the kind that might have complicated its retrieval. [2][3][4] . To our knowledge it has not been described before in the context of vitamin D deficiency and secondary hyperparathyroidism.…”
Section: Commentmentioning
confidence: 99%